2013
DOI: 10.1007/s00449-013-1049-5
|View full text |Cite
|
Sign up to set email alerts
|

Gas hold-up and oxygen mass transfer in three pneumatic bioreactors operating with sugarcane bagasse suspensions

Abstract: Sugarcane bagasse is a low-cost and abundant by-product generated by the bioethanol industry, and is a potential substrate for cellulolytic enzyme production. The aim of this work was to evaluate the effects of air flow rate (QAIR), solids loading (%S), sugarcane bagasse type, and particle size on the gas hold-up (εG) and volumetric oxygen transfer coefficient (kLa) in three different pneumatic bioreactors, using response surface methodology. Concentric tube airlift (CTA), split-cylinder airlift (SCA), and bub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Similar results were obtained by Esperança et al [39] using sugarcane bagasse suspensions, where for all conditions tested the gas holdup was higher in CTA reactors, for the same /. Different results can be observed when comparing the a G values for the three bioreactor models through of superficial gas velocity (U G,R ), since the BC reactors, for example, have a higher rising area which returns lower U G,R values to other reactors for the same air flow rate injected.…”
Section: Global Gas Holdup ( a G )supporting
confidence: 82%
“…Similar results were obtained by Esperança et al [39] using sugarcane bagasse suspensions, where for all conditions tested the gas holdup was higher in CTA reactors, for the same /. Different results can be observed when comparing the a G values for the three bioreactor models through of superficial gas velocity (U G,R ), since the BC reactors, for example, have a higher rising area which returns lower U G,R values to other reactors for the same air flow rate injected.…”
Section: Global Gas Holdup ( a G )supporting
confidence: 82%
“…The two main types of pneumatically agitated bioreactors are gaslift, also known as airlift, and bubble column. Pneumatically agitated bioreactors present several advantages over other multiphase reactors, including low shear stress, simple design, no mechanically moving parts, low energy supply, good mass transfer properties and, low construction and operation costs [143][144][145].…”
Section: Future Promising Bioreactors For Enzymatic Hydrolysismentioning
confidence: 99%
“…Even though this type of bioreactors has still not been used for enzymatic hydrolysis, they represent a promising configuration for the development of enzymatic saccharification, due to the lower energy consumption since they do not require mechanical stirrer to agitate the system. Additionally, pneumatically agitated bioreactors, specifically bubble column bioreactors, gas-lift and fluidized bed bioreactors have been widely used in three-phase systems (gas-liquid-solid) in chemical and biological processes in industry, for example, in cellulolytic and hemicellulolytic enzyme production and, environmental pollution control [145][146][147]. In three-phase systems the gas comes into contact simultaneously with the liquid and solid phases.…”
Section: Future Promising Bioreactors For Enzymatic Hydrolysismentioning
confidence: 99%
“…Cellulase production by filamentous fungi may be achieved through either solid-state fermentation (SSF) or submerged fermentation (SmF). Despite many advantages of SSF over SmF, enzyme production in large-scale SSF bioreactors is hindered by low solids loadings, or if high solids are used, by solids handling and mass and heat transfer gradients during the cultivation process (Barrios-Gonzalez, 2012;Cunha et al, 2012;Esperança et al, 2014). Submerged cultivations with high solids loadings remain challenging since mass transfer and gas hold-up limitations are also compounded by viscosity increases that occur during the first hours of cultivation as a result of fungal growth.…”
Section: Introductionmentioning
confidence: 98%
“…Rheological properties of sugarcane bagasse, specifically, were studied by Geddes et al (2013) and Caldas Pereira et al (2011), who demonstrated that a small amount of enzyme is able to decrease the viscosity of pretreated sugarcane bagasse slurries with improvements in hydrolysis coinciding with improved flow properties. Esperança et al (2014) described hydrodynamic effects of carrying out microbial fermentation in a pneumatic bioreactor system at solids contents between 3% and 20% w/v. The current paper reports enzymatic and microbial liquefaction of steam exploded sugarcane bagasse in a fed-batch system followed by endoglucanase production at high solids loading by an Aspergillus niger wild type strain isolated from the Brazilian biome.…”
Section: Introductionmentioning
confidence: 99%